Konflik Masyarakat Lokal Dengan Pengusaha Pariwisata Terkait Akses Pura Batu Mejan Dan Setra Di Desa Canggu, Kabupaten Badung - Jaya, I Gede Fanny Putra; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 6 No 1 (2018): VOL 6, NO 1 (2018): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2018.v06.i01.p09, 2018)
The growth of accomodation number in Canggu Village is very significant and happen on the seashore. Canggu village is a strategic place for investors to invest today. One of accomodation that has been built by investors in this village is Canggu Intercontinental Hotel. The building process of this hotel experienced many problems caused by violation of agreement between investors and local people. Thus, this research aims to determine the conflicts between local people of Canggu village and tourism investors. This research conducted in Canggu village, Kuta Utara subdistrict, Badung regency. The type of data used is qualitative data. The data source used are primary and secondary data. The data collecting technique used are in-depth interview, observation, and literature study. The method used to determine informants is purposive sampling technique, and the informants are chief of Banjar Canggu and head of orderliness and peacefully section of Kuta Utara subdistrict. This research is limited by concept of agreement, concept of local people, and theory of conflict. The result of this research is that the conflicts between local people and tourism investors about access of Batu Mejan and Canggu cemetery in Canggu village, Badung regency are manifest and latent conflict. The manifest conflict is in the form of road blockade to Canggu Intercontinental Hotel construction which done by local people. The latent conflict is in the form of local issues that emerged among local people which can lead them to do physical actions or manifest conflicts with the investors. Those conflicts are proofs of disagreement between local people and investors regarding to the access of local cemetery and Batu Mejan Temple in Canggu village. Keywords       : Conflicts, Local People, Tourism Investors, Canggu Village .